Sexual and parent–offspring dietary segregation in a colonial raptor as revealed by stable isotopes. (4th February 2016) - Catry, I.; Catry, T.; Alho, M.; Franco, A. M. A.; Moreira, F.
Abstract: Diet composition and foraging behaviour may show considerable variation among population groups (such as sex and age classes), with potentially important consequences for population dynamics. Thus, failure to account for intra‐specific differences in trophic ecology can bias our understanding of different aspects of population ecology and limit the implementation of effective management and conservation strategies. Although countless studies have investigated the diet of birds, comparatively few have tried to describe intra‐specific sources of dietary variation. Here, we used stable isotope analysis (SIA) to investigate sex‐ and age‐related dietary segregation in the lesser kestrel Falco naumanni breeding in South Iberia and to discuss potential mechanisms involved in such segregation. Females had a narrower isotopic niche width and significantly more depleted δ 13 C signatures than males during the courtship period, likely due to a higher consumption of energetically rich mole crickets. Our results suggest that sex‐specific differences in the diet of lesser kestrels do not result from intra‐specific competition and are unlikely to be explained by sexual size dimorphism alone. Instead, the main driving force of observed sexual segregation appears to be the different energetic requirements of males and females before laying, when females need a higher allocation of resources to egg production. δ 15 N isotopic signatures differed significantly between adults and chicks and niche overlap between these age classes was low. Stable isotopic mixing models showed that, compared to adults, the diet of chicks was less diverse and mainly dominated by grasshoppers. Different resource allocation between chicks and adults might also result from different energy requirements, as rapidly growing chicks require more energy than adults, ultimately leading to a parent–offspring dietary segregation. Finally, overall agreement between pellet analysis and SIA methods highlight the potential of SIA for assessing intra‐specific variation in dietary regimes which is often unfeasible through conventional approaches of diet assessment. Abstract : Although countless studies have investigated the diet of birds, comparatively few have described intra‐specific sources of dietary variation. Here, we used SIA to investigate sex‐ and age‐related dietary segregation in the lesser kestrel Falco naumanni . Females showed a narrower isotopic niche width and significantly more depleted δ 13 C signatures than males during the courtship period, likely due to a higher consumption of energetically rich mole crickets driven by selective mate‐feeding behaviour before egg laying. δ 15 N signatures differed significantly between adults and chicks suggesting a parent–offspring dietary segregation during chick rearing. Compared to adults, chicks showed narrower isotopic niches, dominated by grasshoppers. Parents may optimize their investment in offspring by provisioning themselves with different prey than they feed their chicks, as growing chicks usually demand more energy than adult subsistence. Overall agreement between pellet analysis and SIA methods highlight the potential of SIA for assessing intra‐specific variation in dietary regimes.